Coherent Enantiomer‐Selective Population Enrichment Using Tailored Microwave Fields. (2nd August 2017) - Pérez, Cristóbal; Steber, Amanda L.; Domingos, Sérgio R.; Krin, Anna; Schmitz, David; Schnell, Melanie
Abstract: We report the experimental demonstration of coherent enantiomer‐selective enrichment of chiral molecules by employing a novel microwave five‐pulse scheme. Our results show that enantiomers can be selectively transferred to a rotational level of choice by applying sequences of resonant microwave pulses in a phase‐ and polarization‐controlled manner. This is achieved by simultaneously exciting all three kinds of electric dipole‐allowed rotational transitions and monitoring the effect on a fourth rotational transition of choice. Using molecular beams, we apply our method to two chiral terpenes and obtain a 6 % enantiomeric enrichment, which is one order of magnitude larger than that recently reported in a buffer‐gas cell experiment. This approach establishes a robust scheme for controlled manipulation of enantiomers using tailored microwave fields and opens up new avenues for chiral purification and enrichment that can be used in a broad scope of analytical or spectroscopic applications. Abstract : Enantiomerenselektive Anreicherung der Population kann durch simultanes Anregen einer chiralen Probe mit drei orthogonalen Mikrowellenpulsen erreicht werden. Eine sorgfältige Kontrolle der verwendeten Felder ermöglicht den selektiven Transfer von Enantiomeren zu einem Rotationsniveau der Wahl. Zusammen mit weiteren Ergebnissen könnte diese Entdeckung neue Wege in der chiralen Analyse öffnen.